(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Businesses looking to reach younger consumers must grasp the relative efficacy of different techniques in the ever changing advertising market. With an emphasis on the Chandrapur District, this study compares the effects of traditional and animation-based advertising on grabbing young people’s attention, eliciting brand recall, and influencing their purchase intentions. A questionnaire that was semi-structured was given to 100 young people between the ages of 18 and 30 in order to learn more about their preferences and perspectives. This descriptive research approach was used. The results show that, in comparison to traditional advertising, animation-based advertising is thought to be more eye catching, successful in influencing purchase intentions, and improves brand memory. In particular, 61% of participants think that advertisements with animation have a greater influence on purchasing decisions, and 49% think that these advertising increase brand memory. Nonetheless, a sizeable percentage still favours conventional advertising or believes there are no appreciable differences between the two strategies. In order to cater to a range of customer tastes, the research suggests a hybrid marketing approach that blends the dynamic attraction of animation with the tried-and-true dependability of older means.